Truman and Korea : the political culture of the early cold war - Pierpaoli, Paul G., Jr., 1962- (University of Missouri Press, 1999)
"Detailing for the first time the story of America's homefront during the Korean War, Truman and Korea fills an important gap in the historical scholarship of the era. Paul Pierpaoli analyzes the political, economic, social, and international ramifications of America's first war of Soviet containment, never losing sight of the larger context of the Cold War. He focuses on how and why the Truman administration undertook a bloody, inconclusive war on the Korean peninsula while permanently placing the nation on a war footing." "Based upon extensive research in the papers and official presidential files of Harry S. Truman, as well as many manuscript collections and records of wartime and government agencies, Truman and Korea offers a new perspective on the Korean War era and its inextricable ties to broader Cold War decision making."--Jacket